Intraoperative method of femoral head central measurement to prevent leg length discrepancy following hemiarthroplasty - Hu, Hongxin; Lin, Mei; Wu, Xianwei; Lin, Yujin; Lin, Yijun; Chen, Guoli (Frontiers in Surgery, 2023)
Purpose: This study aimed to introduce and investigate the safety and efficiency of the intraoperative central measurement method of the femoral head (IM-CMFH) to prevent leg length discrepancies (LLD) after hemiarthroplasty. Methods: Overall, 79 patients aged 75 to 85 years with femoral neck fractures who underwent hemiarthroplasty were divided into two groups: the Control group (n= 46) and the IM-CMFH group (n = 33). The two groups were compared for postoperative LLD and the proportions of patients with greater than 10 mm, 6-10 mm, and within 5 mm, postoperative femoral offset (FO) difference and the proportions of patients within 5 mm, incremental greater than 5 mm and reduction greater than 5 mm. Next, the vertical distance from the center of the femoral head to the tip of the greater trochanter on the anatomical axis of the femur (VD-CFH-TGTAAF), leg length, and FO on the operative and non-operative sides within the IM-CMFH group. Finally, operative time, hemoglobin loss, Harris score 3 months after surgery, and postoperative complications were analyzed. Results: Compared with the control group, the postoperative LLD and FO differences were significantly lower in the IM-CMFH group (P=0.032; P=0.012), and the proportion of patients with postoperative LLD greater than 10 mm decreased significantly (P=0.041), while the proportion of patients with FO difference of within 5 mm increased (P=0.009). In addition, there was no significant difference in the operative time, hemoglobin loss, and Harris score at 3 months postoperatively and postoperative complications between the two groups (P>0.05). No significant difference in FO, leg-length, and VD-CFH-TGTAAF difference between the operative and non-operative sides within the IM-CMFH group (P>0.05). Conclusion: Satisfactory results can be achieved by using the IM-CMFH to prevent LLD following hemiarthroplasty, and there is no increase in operative time, hemoglobin loss, or postoperative complications. This technique is efficient for hemiarthroplasties and is both simple and convenient.